Asymmetric Drug-Induced Parkinsonism and Psychopathology: A Prospective Naturalistic Study in Long-Stay Psychiatric Patients - Pieters, Lydia E.; Bakker, P. Roberto; van Harten, Peter N. (Frontiers in Psychiatry, 2018)
Background: Drug-induced parkinsonism (DIP) is the most common movement disorder induced by antipsychotics. Although DIP is mostly symmetric, asymmetric DIP is reported in a substantial part of the patients. We investigated the frequency of motor asymmetry in DIP and its relationship to the severity of psychopathology in long-stay psychiatric patients. Methods: We obtained data from a cohort study of 207 long-stay psychiatric patients on the frequency and risk factors of tardive dyskinesia, akathisia, tardive dystonia, and DIP. From July 2003 - May 2007 (mean follow-up 1.1 year) drug-induced movement disorders were assessed at least two times in each patient, with a frequency of persistent DIP of 56.2%. All patients that had at least one time parkinsonism in the upper/lower limb(s) were included for analyses (190 patients, 79 women; mean age 48.0±12.9 years). The Unified Parkinson Disease Rating Scale (UPDRS) motor scale was used to calculate the frequency of asymmetric parkinsonism. Multilevel mixed models were built to explore the relationship between asymmetry in parkinsonism and the severity of psychopathology, measured on the Clinical Global Impression-Schizophrenia scale severity index (CGI-SCH SI). Results: The frequency of asymmetric parkinsonism was 20.8%. Asymmetry in parkinsonism was associated with symptom severity on all CGI-SCH SI scales (β range 0.37 - 3.74), and significantly associated with the positive symptom scale (β 3.74, 95%CI= 0.35 – 7.31). Conclusion: DIP is asymmetric in a substantial part of patients. Asymmetric presentation of DIP is of clinical relevance as it is related to the severity of psychopathology, and may alert the clinician of more severe psychopathology. Future research is recommended to provide insight into the neuropsychopathology and clinical value of asymmetric parkinsonism for psychiatric patients.